The complete mitochondrial genome of Sardinops sagax (Jenyns, 1842) (Clupeiformes: Clupeidae) and phylogenetic analyses of sardines - Fenghua Tang; Weitao Chen (Mitochondrial DNA. Part B. Resources, 2021)
Pacific sardine Sardinops sagax (Jenyns, 1842), a sardine species that widely distributes in Pacific, is an important commercial species in many areas. In this study, we characterized the complete mitochondrial genome of S. sagax using next generation sequencing technology. The complete mitogenome of S. sagax was 16,883 base pairs (bp) in length and comprised 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 ribosomal RNA genes (rRNA), and one control region (D-loop). Phylogenetic analysis indicated that sardine species included three clades (I, II and III) and S. sagax clustered with Sardinops melanostictus.